Estrategias de enseñanza y logro de aprendizaje en estudiantes del área de personal social en la Institución Educativa Nº 60816 Almirante Miguel Grau, Yaquerana 2023 - Silvano Manuyama, Luz Erlinda (2024)
This study had the intention of diagnosing the relationship between teaching strategy and level of learning achievement in students in the area of Social Personnel at the Primary Secondary Educational Institution No. 60816 'Almirante Miguel Grau', Yaquerana, 2023. Quantitative framing inquiry without experiment, detailed type and cross design. The population was 83 participants and the test was defined by 69 primary education students from the Primary Secondary Educational Institution No. 60816 'Almirante Miguel Grau', Yaquerana, 2023. The technique used to collect data was the interview and documentary archive, the instruments handled were the question form and the evaluation minutes. The data were processed using the SPSS statistical package, edition 29 in Spanish and the Excel calculation tool. The inferential statistical test Chi Square (X2) with α = 0.05% and 0.95% confidence level was used to analyze and interpret the information. The non parametric test of the Spearman coefficient with a result of 0.7165, which indicates a high degree of correlation; allowed us to accept the thesis that there is a relationship between teaching strategy and level of learning achievement in students in the area of Social Personnel in the Primary Secondary Educational Institution Nº60816 'Almirante Miguel Grau', Yaquerana, 2023.